Adverse prognostic impact of complex karyotype (≥3 cytogenetic alterations) in adult T-cell acute lymphoblastic leukemia (T-ALL). (October 2021) - Genescà, Eulàlia; Morgades, Mireia; González-Gil, Celia; Fuster-Tormo, Francisco; Haferlach, Claudia; Meggendorfer, Manja; Montesinos, Pau; Barba, Pere; Gil, Cristina; Coll, Rosa; Moreno, María-José; Martínez-Carballeira, Daniel; et al.
Highlights: We defined Complex Karyotype (CK) in T-ALL as the presence of ≥3 cytogenetic alterations. T-ALL cases with CK ≥ 3 accounted for 16 % (22/139) of all evaluable karyotypes. T-ALL patients with CK ≥ 3 showed a significantly inferior response to initial therapy. CK ≥ 3 showed an adverse prognostic value in a multivariable test, independently of MRD. The mutational profile CK ≥ 3 patients suggested a molecular mechanism of resistance. Abstract: The potential prognostic value of conventional karyotyping in adult T-cell acute lymphoblastic leukemia (T-ALL) remains an open question. We hypothesized that a modified cytogenetic classification, based on the number and type of cytogenetic abnormalities, would allow the identification of high-risk adult T-ALL patients. Complex karyotype defined by the presence of ≥3 cytogenetic alterations identified T-ALL patients with poor prognosis in this study. Karyotypes with ≥3 abnormalities accounted for 16 % (22/139) of all evaluable karyotypes, corresponding to the largest poor prognosis cytogenetic subgroup of T-ALL identified so far. Patients carrying karyotypes with ≥3 cytogenetic alterations showed a significantly inferior response to therapy, and a poor outcome in terms of event-free survival (EFS), overall survival (OS) and cumulative incidence of relapse (CIR), independently of other baseline characteristics and the end-induction minimal residual disease (MRD) level. Additional molecular analyses of patients carrying ≥3 cytogenetic alterations showed a unique molecular profile that could contribute to understand the underlying molecular mechanisms of resistance and to evaluate novel targeted therapies ( e.g. IL7R directed) with potential impact on outcome of adult T-ALL patients.